2022
DOI: 10.1101/2022.05.31.494017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting higher-order mutational effects in an RNA enzyme by machine learning of high-throughput experimental data

Abstract: Ribozymes are RNA molecules that catalyze biochemical reactions. Self-cleaving ribozymes are a common naturally occurring class of ribozymes that catalyze site-specific cleavage of their own phosphodiester backbone. In addition to their natural functions, self-cleaving ribozymes have been used to engineer control of gene expression because they can be designed to alter RNA processing and stability. However, the rational design of ribozyme activity remains challenging, and many ribozyme-based systems are engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A deeper analysis of the data is still needed to examine whether possible higher-order epistatic interactions are at play in these variants. Beck et al used a machine-learning model based on a high-throughput data set of the effects of mutations in the CPEB3 self-cleaving ribozyme to predict the activity of CPEB3 variants . The authors found that the model trained with pairwise interactions could predict active sequences at high mutational distances.…”
Section: Combinatorial Challenges In Enzyme Engineering and Computati...mentioning
confidence: 99%
See 3 more Smart Citations
“…A deeper analysis of the data is still needed to examine whether possible higher-order epistatic interactions are at play in these variants. Beck et al used a machine-learning model based on a high-throughput data set of the effects of mutations in the CPEB3 self-cleaving ribozyme to predict the activity of CPEB3 variants . The authors found that the model trained with pairwise interactions could predict active sequences at high mutational distances.…”
Section: Combinatorial Challenges In Enzyme Engineering and Computati...mentioning
confidence: 99%
“…Trained with higher-order interactions, the correlation of predicted and measured activity could be increased for higher mutational distances. 124 In 2022, Giessel et al used a VAE approach to successfully engineer an ornithine transcarbamylase for increased catalytic activity and thermal stability, as a potentially therapeutically relevant enzyme against a rare metabolic disease. The authors pointed out that higher-order coevolutionary effects have the potential to provide a deeper understanding of the structure− function relationship in novel ways.…”
Section: Deep-learning Modelsmentioning
confidence: 99%
See 2 more Smart Citations